Analysis of Pharmacokinetics in the Cochlea of the Inner Ear - Sawamura, Seishiro; Ogata, Genki; Asai, Kai; Razvina, Olga; Ota, Takeru; Zhang, Qi; Madhurantakam, Sasya; Akiyama, Koei; Ino, Daisuke; Kanzaki, Sho; Saiki, Takuro; Matsumoto, Yoshifumi; et al. (Frontiers in Pharmacology, 2021)
Hearing loss affects >5% of the global population and therefore, has a great social and clinical impact. Sensorineural hearing loss, which can be caused by different factors, such as acoustic trauma, aging, and administration of certain classes of drugs, stems primarily from a dysfunction of the cochlea in the inner ear. Few therapeutic strategies against sensorineural hearing loss are available. To develop effective treatments for this disease, it is crucial to precisely determine the behavior of ototoxic and therapeutic agents in the microenvironment of the cochlea in live animals. Since the 1980s, a number of studies have addressed this issue by different methodologies. However, there is much less information on pharmacokinetics in the cochlea than that in other organs; the delay in ontological pharmacology is likely due to technical difficulties with accessing the cochlea, a tiny organ that is encased with a bony wall and has a fine and complicated internal structure. In this review, we not only summarize the observations and insights obtained in classic and recent studies on pharmacokinetics in the cochlea but also describe relevant analytical techniques, with their strengths, limitations, and prospects.